Teknologi Informasi dalam Pemasaran guna Meningkatkan Usaha Mikro Kecil dan Menegah di Desa Cicalengka Kecamatan Pagedangan Kabupaten Tangerang - Sulistiani, Sinta; Andalusi, Ratih; Wulansari, Retno (Jurnal PKM Manajemen Bisnis, 2025)
The growth of digital technology offers great potential for supporting Micro, Small, and Medium Enterprises (MSMEs), especially in rural regions where digital literacy remains limited. Many business actors in these areas struggle to utilize information technology effectively for marketing purposes. To respond to this challenge, a community service program (PKM) titled "Information Technology in Marketing to Improve Micro, Small, and Medium Enterprises in Cicalengka Village, Pagedangan District, Tangerang Regency" was carried out. The program aimed to enhance the marketing capabilities of local entrepreneurs through the application of digital tools. Conducted on April 19, 2025, in Cicalengka Village, the activity involved 10 lecturers from Pamulang University and was attended by 21 MSME practitioners from the local community. The PKM employed a combination of learning methods, including material presentation, hands-on training, interactive discussions, and question-and-answer sessions. Participants received guidance on optimizing social media, online sales platforms, and digital branding techniques. The results showed an increase in participants’ understanding of digital marketing and their readiness to implement it in daily business operations. This initiative plays a role in supporting MSME competitiveness and sustainability in the face of ongoing digital transformation.